Optimization of fat, oil, and grease biodegradation using bacteria isolated from palm oil mill effluent - Alqedra, Fadi I. A. (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Biodegradation of fat, oil, and grease (FOG) plays an important role in water pollution control and wastewater management. However, many food services establishments generate FOG-containing wastewater which there is no accepted technology for its treatment. FOG is the causative agent of blockage sewer systems, and results in sanitary sewer overflows (SSO). To solve this problem, this study evaluated the feasibility of FOG-degrading microorganism on the biodegradation of palm oil. Six strains capable of degrading FOG were isolated from palm oil mill effluent (POME). The potential bacterial strains were selected based on Tween-80-degrading ability. Micrococcus lylae strain DSM 20315 showed the highest growth compared to the other strains. Hence, it was selected for FOG degradation test. The biodegradability was performed as a function of pH (6, 7, 8), initial oil concentration (1, 3, 5% v/v), and bacterial inoculum concentration (2, 6, 10% v/v). Optimization of these parameters of palm oil degradation was studied. A 2 level factorial design was used to investigate the influence of these three parameters. The maximum oil degradation was 68% obtained at pH 6, initial oil concentration 1 mL, and bacterial inoculum concentration of 10 mL. The lowest oil degradation obtained was 22%. The initial oil concentration followed by bacterial inoculum concentration enhanced the removal efficiency of FOG, but the pH level did not significantly promote the degradation rate. As a result, the optimum process conditions for maximizing oil degradation (removal) were recognized as follows: pH 6, initial oil concentration 1 mL and bacterial inoculum concentration of 10 mL. The result indicated that the use if isolated Micrococcus lylae strain DSM 20315 in bio-augmenting grease trap or other process might possibly be sufficient to acclimate biological processes for FOG degrading.